2021
DOI: 10.22456/2316-2171.98707
|View full text |Cite
|
Sign up to set email alerts
|

Idosos Com Hiv/Aids: Uma Revisão Integrativa

Abstract: Introdução: O número de casos de HIV (Vírus da Imunodeficiência Humana) e da Síndrome da Imunodeficiência Adquirida (Aids) em idosos tem aumentado, boa parte em função do sexo sem proteção e da vida sexual ativa prolongada, por meio da reposição hormonal e das medicações para impotência sexual. Conhecer o que está sendo pesquisado sobre o assunto pode contribuir para uma assistência qualificada. Objetivo: Analisar as produções científicas publicadas sobre idosos com HIV/Aids. Metodologia: Trata-se de uma revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Accordingly, the question that guided this research was: What were the coping strategies adopted by the elderly individuals, throughout their lives, to overcome the difficulties experienced by the condition of being a person with HIV? Systematic integrative review, which systematized the production on HIV in the elderly population, concluded that most research brings data related to the clinical profile, with epidemiological studies, of a quantitative nature, with few studies focused on the experiences or the more subjective and qualitative elements of living with HIV as an elderly person, which is an epistemological gap that needs to be investigated 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the question that guided this research was: What were the coping strategies adopted by the elderly individuals, throughout their lives, to overcome the difficulties experienced by the condition of being a person with HIV? Systematic integrative review, which systematized the production on HIV in the elderly population, concluded that most research brings data related to the clinical profile, with epidemiological studies, of a quantitative nature, with few studies focused on the experiences or the more subjective and qualitative elements of living with HIV as an elderly person, which is an epistemological gap that needs to be investigated 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, a questão que balizou a realização desta pesquisa foi: Quais foram as estratégias de enfrentamento adotadas pelos idosos, no percurso de suas vidas, para superar as dificuldades vivenciadas pela condição de ser uma pessoa com HIV? Revisão sistemática integrativa, que sistematizou a produção sobre HIV em idosos, concluiu que a maioria das pesquisas traz dados relacionados ao perfil clínico, com estudos de caráter epidemiológico, de natureza quantitativa, com poucas pesquisas que se debruçam sobre as vivências ou os elementos mais subjetivos e qualitativos de viver com HIV enquanto pessoa idosa o que se configura numa lacuna epistemológica que precisa ser investigada 6 .…”
Section: Introductionunclassified